2021
DOI: 10.33068/iccd.vol3.iss1.372
|View full text |Cite
|
Sign up to set email alerts
|

Assistance of Creativity Children in Growing Awareness of the 5m Protocols in the Time of Covid 19

Abstract: The increase in the corona or covid 19 pandemic in Indonesia is no longer something to be taken lightly. With many cases of spread and addition in South Jakarta the most recorded in the Kebayoran Lama area. It is possible that many people still do not understand the importance of the 5M concept as a protocol to break the chain of spreading the virus. This community service is carried out for TKAU children in Ulujami, South Jakarta. This segmentation of the selection of children as a basis for education and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The only method to reduce the transmission of COVID-19 is by implementing health protocols. These health protocols consist of wearing a face mask, washing hands using soap, maintaining physical distancing, avoiding gathering or crowds, and reducing mobilization [ 4 , 5 ]. Oh et al, 2020 [ 6 ], indicated that proper health protocol practices can minimize COVID-19 transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The only method to reduce the transmission of COVID-19 is by implementing health protocols. These health protocols consist of wearing a face mask, washing hands using soap, maintaining physical distancing, avoiding gathering or crowds, and reducing mobilization [ 4 , 5 ]. Oh et al, 2020 [ 6 ], indicated that proper health protocol practices can minimize COVID-19 transmission.…”
Section: Introductionmentioning
confidence: 99%